Oral anticoagulation with edoxaban - Ahrens, I.; Bode, C. (Hämostaseologie, 2012)
Edoxaban (the former DU176b) an orally available direct factor Xa inhibitor has been engineered from DX-9065a, which was one of the first parenteral Xa inhibitors. Edoxaban has a time to peak plasma concentrations of 1–2 hours and a half-life of approximately 10 hours after multiple doses. Edoxaban is the third new oral anticoagulant in the group of direct factor Xa inhibitors that has gained clinical approval for the prevention of venous thromboembolism after major orthopaedic surgery. Currently, edoxaban is assessed in late stage clinical development for the prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation (ENGAGE AF-TIMI 48, NCT00781391) and for the treatment and prevention of venous thromboembolism in patients with acute deep vein thrombosis and/or pulmonary embolism (HOKUSAI VTE, NCT00986154).Both clinical phase III trials represent the largest single clinical studies in their entity so far with an enrolment of 21 107 patients in ENGAGE AF-TIMI 48 and a planned enrolment of 7500 patients in HOKUSAI VTE.The pharmacological properties of edoxaban will be discussed along with the current late stage clinical development focusing on the prevention of stroke and venous thromboembolism.
Keywords: Edoxaban; oral anticoagulants; FXa inhibitor; thrombosis; atrial fibrillation; stroke; VTE; PE